PENGEMBANGAN BAHAN AJAR TEKS PROSEDUR BERBASIS KEARIFAN LOKAL PIDIE DI SD/MI - Hizriani, Niswatul; Mulia; Cut Atthahirah; Ridwan Daud; Iin Nurhaliza (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop procedural text teaching materials based on the local wisdom of Pidie for elementary school level. This research used the Research and Development (R&D) method with the ADDIE model which consists of analysis, design, development, implementation, and evaluation stages. The research subjects included material experts, media experts, language experts, teachers, and fifth grade students of MIN 18 Pidie. The data collection techniques were carried out through validation sheets and response questionnaires. The results showed that the validation score from the material expert was 90%, the media expert was 96%, and the language expert was 93%, all categorized as very valid. The results of the teacher response questionnaire obtained a percentage of 92% with a very practical category, while the student response questionnaire obtained a percentage of 90% with a very practical category. Thus, the procedural text teaching materials based on the local wisdom of Pidie that were developed are declared feasible and appropriate to be used in Indonesian language learning in elementary schools (SD/MI).